2020
DOI: 10.1155/2020/8863960
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Variation of Friction Coefficient of Sandstone Joint in Sliding

Abstract: The friction coefficient of rock joints is closely related to the stability of the slope. However, it is difficult to predict the friction coefficient due to the influence of surface roughness and mechanical properties of rocks. In this study, we use a method that combines theoretical analysis with a sandstone sliding friction test and propose a model to predict the friction coefficient of Sandstone Joint. A sandstone sliding friction test was performed on a self-made reciprocating sliding friction test device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Therefore, γðtÞ = 1. Accordingly, the expression for DðtÞ can be obtained by substituting Equations ( 16)- (18) into Equation (15).…”
Section: Geofluidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, γðtÞ = 1. Accordingly, the expression for DðtÞ can be obtained by substituting Equations ( 16)- (18) into Equation (15).…”
Section: Geofluidsmentioning
confidence: 99%
“…Zhou et al [13] and Song et al [14] summarized the displacement response law and stress wave propagation law of different parts of weak surface under blasting load. Zhao et al [15] combined theoretical analysis with the sandstone sliding friction test to propose a model to predict the friction coefficient of sandstone joint. The results showed that the larger the wear mass, the larger the friction coefficient in sliding, and the larger the wear area, the smaller the friction coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have carried out research to study the influence of different factors on the shear characteristics of jointed rock mass, including joint inclination [1], joint roughness [2,3], rock bridge [4,5], shear rate [6], normal stress [7], friction coefficients [8], and temperature [9].…”
Section: Introductionmentioning
confidence: 99%